The generals of Pakistan and Bangladesh - Ahmad, Borhanuddin (New Delhi : Vikas Publishing House, 1993)
Political scenario of Pakistan and Bangladesh and roles of their generals.
Includes bibliographical references (pages [199]-201).
Donated By Akbar Ali Khan
Keywords: Generals -- Political activity -- Pakistan; Generals -- Political activity -- Bangladesh; Pakistan -- Politics and government; Pakistan -- Armed Forces -- Political activity; Bangladesh -- Politics and government; Bangladesh -- Armed Forces -- Political activity